Clinicopathological Characteristics ofRETRearranged Lung Cancer in European Patients. Issue 1 (January 2016) - Michels, Sebastian; Scheel, Andreas Hans; Scheffler, Matthias; Schultheis, Anne Maria; Gautschi, Oliver; Aebersold, Franziska; Diebold, Joachim; Pall, Georg; Rothschild, Sacha; Bubendorf, Lukas; Hartmann, Wolfgang; Heukamp, Lukas; et al.
ABSTRACT : Introduction : Rearrangements of RET are rare oncogenic events in patients with non–small cell lung cancer (NSCLC). While the characterization of Asian patients suggests a predominance of nonsmokers of young age in this genetically defined lung cancer subgroup, little is known about the characteristics of non‐Asian patients. We present the results of an analysis of a European cohort of patients with RET rearranged NSCLC. Methods : Nine hundred ninety‐seven patients with KRAS/EGFR/ALK wildtype lung adenocarcinomas were analyzed using fluorescence in situ hybridization for RET fusions. Tumor specimens were molecularly profiled and clinicopathological characteristics of the patients were collected. Results : Rearrangements of RET were identified in 22 patients, with a prevalence of 2.2% in the KRAS/EGFR/ALK wildtype subgroup. Co‐occurring genetic aberrations were detected in 10 patients, and the majority had mutations in TP53 . The median age at diagnosis was 62 years (range, 39–80 years; mean ± SD, 61 ± 11.7 years) with a higher proportion of men (59% versus 41%). There was only a slight predominance of nonsmokers (54.5%) compared to current or former smokers (45.5%). Conclusions : Patients with RET rearranged adenocarcinomas represent a rare and heterogeneous NSCLC subgroup. In some contrast to published data, we see a high prevalence of current and former smokers in our white RET cohort. The significance of co‐occurring aberrations, so far, is unclear.